Single incision laparoscopic appendectomy: A prospective study - Nilesh P Mangam (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Appendicitis is one of the common pathologies encountered in surgical practice. Except in minority of the cases, the treatment is usually surgical. Till recent past, open appendectomy has been the procedure of choice for appendicitis. With increasing expertise in laparoscopic surgeries more and more surgeons are utilizing the laparoscopic approach for appendectomy. Laparoscopic surgeries have distinct advantages such as less surgical trauma, improved and quick postoperative recovery, and esthetic results. Single-incision laparoscopic surgery (SILS) is rapidly gaining acceptability in young population because of its cosmetic advantages. Moreover, these surgeries also avoid the risk of port-site hernias and the possibility of wound infection.